Mental, Social-Psychological Stimulation and Nutritional Suplementation Affects Stunting Incidence among Children in Indonesia - Utami, Ressa Andriyani; Juliani, Enni (Jurnal Kesehatan Holistic, 2020)
Stunting is a public health problem regarding nutritional status that is diagnosed through a long body based on a standard deviation of minus two. One effort that can be done by families in overcoming the problem of stunting is through optimization of Mental Stimulation, Nutrition Supplementation and Social Psychological Stimulation (MeNu SoP). The purpose of this study was to determine the effectiveness of Mental Stimulation, Nutritional Supplementation and Social Psychological Stimulation on the incidence of stunting in children. The study design used quasi pre and post test experiments without control groups. The number of research samples as many as 40 respondents were selected using cluster sampling techniques. The results showed significant changes in the variable Mental Stimulation before and after the intervention (p value = 0,000), Nutritional Supplementation before and after the intervention (p value = 0,000), Social Psychological Stimulation (p value = 0,000), and anthropometric status before and After the intervention (p value = 0,000). The application of MeNu SoP can be used by families, nurses and other health workers to improve the status of anthropometric toddlers with stunting.